What we know about political parties’ organization: an evaluation of one hundred years of literature - Amaral, Oswaldo (2013)
Political parties have been acknowledged as essential organizations for the functioning of democratic regimes. Because of that, Political Science has developed a long tradition in analysing and explaining how these organizations work and evolved over time. Since the work of Robert Michels, published in 1911, scholars have been asking themselves the following questions: How does the decision making process work inside the parties? How and why political parties change? The main aim of this paper is to review and discuss the main contributions of Political Science, both abroad and in Brazil, to the study of party organization. In order to do that, we focus on the works that analysed the internal functioning of political parties and the relationship between parties, their members and other civil society organizations.